2014
DOI: 10.1093/wbro/lku005
|View full text |Cite
|
Sign up to set email alerts
|

Labor Market Regulations: What do we know about their Impacts in Developing Countries?

Abstract: Labor market regulation is a high-profile, and often contentious, area of public policy. Although these regulations have been studied most extensively in developed countries, there is a growing body of literature on their effects in developing countries. This paper reviews that literature and focuses on the impacts of two important types of labor market regulation, minimum wages and employment protection legislation (EPL), on employment, earnings, and productivity. Strong and opposing views exist regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 72 publications
0
33
0
1
Order By: Relevance
“…Gordon Betcherman (2014: 12), conducting a comprehensive review of theoretical studies, concluded that ‘[e]conomic theory does not lead to clear predictions about the employment effects of (EPL) [employment protection law]’. In this section, I will outline the basic reasoning underpinning the post-Keynesian and new institutional arguments that have contested the neoclassical position that increased protection dampens employment creation, and draw attention to some empirical research that supports these claims.…”
Section: Introductionmentioning
confidence: 99%
“…Gordon Betcherman (2014: 12), conducting a comprehensive review of theoretical studies, concluded that ‘[e]conomic theory does not lead to clear predictions about the employment effects of (EPL) [employment protection law]’. In this section, I will outline the basic reasoning underpinning the post-Keynesian and new institutional arguments that have contested the neoclassical position that increased protection dampens employment creation, and draw attention to some empirical research that supports these claims.…”
Section: Introductionmentioning
confidence: 99%
“…Other issues, such as high tax burdens, confused labor laws that imprison the relationship between companies and workers are among some problems the government needs to handle (Betcherman, 2014;De Moura & Barreira, 2015).…”
Section: Alternatives To Circumvent the Current Economic Fatigue In Bmentioning
confidence: 99%
“…Betcherman et al . () analyse the Youth Employment Inventory, a database of worldwide youth employment interventions released by the World Bank. 39% of interventions were skills‐based, with subsidies constituting approximately 12% overall.…”
Section: Background To the Eti In South Africa And International Evidmentioning
confidence: 99%